Predicting a firm's forecasting ability: the roles of organizational illusion of control and organizational attention - Durand, Rodolphe (Strategic Management Journal, 2003)
Abstract Recent research shows that forecasting ability is an organizational distinctive competence. We propose and test a model accounting for interfirm differences in forecasting ability. After controlling for reciprocal effects, we find that two principal firm‐level factors (i.e., organizational illusion of control and organizational attention) influence both bias and magnitude of errors in estimates. High organizational illusion of control increases positive forecast bias. As for organizational attention, higher relative investments in market information appear to reduce positive forecast bias and magnitude of errors; they also moderate forecast bias due to illusion of control. Finally, higher relative investments in employee capability increase both negative forecast bias and, unexpectedly, magnitude of errors for the majority of observed cases. Copyright © 2003 John Wiley & Sons, Ltd.